IMPROVING STUDENTS’ READING COMPREHENSION BY USING LITERARY WORK - Aidil Fitrah Rustan; Ummi Khaerati Syam; Herlina Daddi (FKIP Unismuh Makassar, 2021)
This research aimed at finding out students’ literal reading comprehension by using literary work as a Media. The researcher employed a pre-experimental design, in which pre-test and post-test comparison was used to find out whether the used literary work Media enhance the students’ reading skill, the population of the research was all students of the eleventh grade students of SMA Negeri 1 Gowa which consisted of three classes. The sample was class XI Bahasa which consisted of 28 students’ by using cluster sampling technique. The instruments of this research was reading test. To analyze the score of the students’ achievement in pre-test and post-test the researcher used t-test analyzes. The result of the data showed that there was a significant difference between pre-test and post-test. The value of t-test in terms of main idea was 12.1 and fsupporting detail was 12.5. There figure was greater than the t-table (1.729) at the level of significant (p) = 0.05 degree of freedom (df) = 18. Therefore, it can be said that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. It means that there was a significant difference between the students’ reading skill before and after using literary work as a media or it can be stated that the use of literari work as a media was effective in improving students’ reading skill at eleventh grade students of SMA Negeri 1 Gowa.